Penampilan fenotipik sifat-sifat produksi danreproduksi kambing peranakan etawah - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
,. .The objective of this research was to investigate the potency of production and reproductive characteristics of Etawah crossbreed (EC) goat, raized at Goat Breeding Center "Sumber Rejo" Kendal, Central Java. The parameters measured were birth percentage, female:male ratio, age of maturity, period of pregnancy, kidding internal, and mortality. The results showed that average weights (kg) of female goats at birth, weaned, and mature were 2,53, 10.53 and 23.38. respectively, whereas for male goat were 2.80 (at birth) and 11.30 (at weaned). The average of birth weights (kg) for single, twin on triple were 3.13, 2.75 and 2.11. The weaning weight (kg) were 12.12, 10.82 and 10.43, respectively. The mature weight (kg) for female goat was 24.95 (single), 24.95 (twin) and 24.25 (triple). The percentages of birth for EC goat were 137.7, 64.4 (single), 33.5 (twin) and 2.1 (triple). The ratio for male:female was 49.8%. The female mature weight was 298.9 days, whereas period of pregnancy was 149.5 days, and kidding interval was 221 days. Mortality was found as much as 17.7% for kid, and 56.5% for the population. (Key words: Body weight, Reproduction, Etawah Crossbred Goat